2015
DOI: 10.1253/circj.cj-15-0217
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Presentation, Management and Outcome of Japanese Patients With Acute Myocardial Infarction in the Troponin Era – Japanese Registry of Acute Myocardial Infarction Diagnosed by Universal Definition (J-MINUET) –

Abstract: on behalf of the J-MINUET investigators Background: New criteria for diagnosis of acute myocardial infarction (AMI) were proposed in 2000 as a universal definition, in which cardiac troponin (cTn) was the preferred biomarker. A large number of patients formerly classified by creatine kinase (CK) as unstable angina are now ruled-in by cTn as non-ST-elevation myocardial infarction (NSTEMI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 25 publications
4
65
3
2
Order By: Relevance
“…The design, inclusion criteria, and results of the J-MINUET study have been previously reported. 15 Briefly, AMI was diagnosed using the new universal definition, in which cardiac troponin is the preferred biomarker of myocardial injury. 16 ST-segment elevation AMI was diagnosed in the presence of new ST elevation at the J point in at least 2 contiguous leads ≥0.2 mV in men or ≥0.15 mV in women in leads V2-3, or ≥0.1 mV in another 2 contiguous leads.…”
Section: Methodsmentioning
confidence: 99%
“…The design, inclusion criteria, and results of the J-MINUET study have been previously reported. 15 Briefly, AMI was diagnosed using the new universal definition, in which cardiac troponin is the preferred biomarker of myocardial injury. 16 ST-segment elevation AMI was diagnosed in the presence of new ST elevation at the J point in at least 2 contiguous leads ≥0.2 mV in men or ≥0.15 mV in women in leads V2-3, or ≥0.1 mV in another 2 contiguous leads.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with a diagnosis of AMI at presentation to hospital have been enrolled and followed up continuously. The aims of the KAMIR-NIH are as follows: (1) to collect data on baseline clinical characteristics, current treatment patterns, and shortand long-term patient outcomes; (2) to analyze the prognostic factors of AMI; and (3) to improve the long-term prognosis of individual patients.…”
Section: Objectives Of the Registrymentioning
confidence: 99%
“…1- 7 Recently, PCI has become a widely used therapeutic approach for the treatment of AMI patients. 8- 10 As compared with fibrinolytic therapy, PCI has better clinical outcomes in terms of higher success rates of infarct vessel reperfusion and greater reduction of infarct area. 8 Clinically, these benefits likely result in a lower incidence of recurrent ischemia, re-infarction, and heart failure, and, consequently, an improved survival rate.…”
Section: Data Collectionmentioning
confidence: 99%